Modulation of proteoglycan receptor PTPσ enhances MMP-2 activity to promote recovery from multiple sclerosis. Issue 1 (December 2018) - Luo, Fucheng; Tran, Amanda; Xin, Li; Sanapala, Chandrika; Lang, Bradley; Silver, Jerry; Yang, Yan
Abstract Multiple Sclerosis (MS) is characterized by focal CNS inflammation leading to the death of oligodendrocytes (OLs) with subsequent demyelination, neuronal degeneration, and severe functional deficits. Inhibitory chondroitin sulfate proteoglycans (CSPGs) are increased in the extracellular matrix in the vicinity of MS lesions and are thought to play a critical role in myelin regeneration failure. We here show that CSPGs curtail remyelination through binding with their cognate receptor, protein tyrosine phosphatase σ (PTPσ) on oligodendrocyte progenitor cells (OPCs). We report that inhibition of CSPG/PTPσ signaling by systemically deliverable Intracellular Sigma Peptide (ISP), promotes OPC migration, maturation, remyelination, and functional recovery in animal models of MS. Furthermore, we report a downstream molecular target of PTPσ modulation in OPCs involving upregulation of the protease MMP-2 that allows OPCs to enzymatically digest their way through CSPGs. In total, we demonstrate a critical role of PTPσ/CSPG interactions in OPC remyelination in MS. Demyelination failure in multiple sclerosis (MS) may contribute to the disease progression. This study shows that chondroitin sulfate proteoglycans (CSPGs) can inhibit remyelination in an animal model of MS via CSPG binding with the receptor PTPσ on oligodendrocyte progenitor cells, and disruption of this interaction can promote recovery in the animal models of MS.